THE RELATIONSHIP BETWEEN WAITING TIMES FOR MEDICATION SERVICES AND SERVICE QUALITY AND OUTPATIENT SATISFACTION AT NENE MALLOMO HOSPITAL SIDENRENG RAPPANG REGENCY - Karmila Kadir; Pratiwi Ramlan; Mardhatillah; Zulkarnain Sulaeman (CV. Fahr Publishing, 2026)
Pharmaceutical dispensing services serve as an indicator of medical service quality, particularly regarding patient safety and satisfaction. At Nene Mallomo Regional General Hospital (RSUD), there is a discrepancy between the 2024 target of 95% and the actual achievement of 85%, indicating that service quality is currently inadequate. This quality gap has the potential to impact patient satisfaction levels. This study aims to analyze the relationship between medication dispensing waiting times, service quality, and outpatient satisfaction at Nene Mallomo RSUD, Sidenreng Rappang Regency. The study employed an observational analytic design. A sample of 98 respondents was determined using Slovin's formula with a 10% margin of error. Data were collected through surveys and observations, followed by analysis using univariate methods and the bivariate Chi-square test. The results indicate a significant relationship between waiting time and patient satisfaction (p = 0.001) however, no significant relationship was found between service quality and patient satisfaction (p = 0.250). This study provides a valuable basis for hospital management to evaluate and optimize medication dispensing services.